Perfectly confident : how to calibrate your decisions wisely - Moore, Don A., 1970- (Harper Business, an imprint HarperCollins Publishers, 2020)
"Is confidence always a good thing? Don Moore, Professor of Management of Organizations at the Haas School of Business, argues that confidence is good, but overconfidence can hinder growth."--